ZnO-Nanorods as an Efficient Heterogeneous Catalyst for the Synthesis of Thiazole Derivatives in Water - Shams-Najafi, Sayyed J.; Gholizadeh, Mostafa; Ahmadpour, Ali; Rostami-Charati, Faramarz (Combinatorial Chemistry & High Throughput Screening, 2017)
Aims & Scope: Thiazole derivatives are produced using one-pot multicomponent reactions of acid chlorides, potassium thiocyanate, amino acids, alkyl bromides and ZnO nanorods (NR-ZnO) as the catalyst in water at ambient temperature. These reactions were no't performed without using NR-ZnO as the catalyst. Nanorods of ZnO have been prepared by reflux procedure using sodium dodecylsulfate (SDS). Nanorods of ZnO showed a considerable improvement in the yield of the product and displayed significant reusable activity. Materials and Methods: In these reactions, all chemicals were prepared from Fluka (Buchs, Switzerland). Nanorods of ZnO were synthesized in the laboratory according to literature report. By using an electrothermal 9100 apparatus, melting points of synthesized compounds were determined. Heraeus CHN-O-Rapid analyzer was employed for elemental analyses for C, H, and N. FINNIGANMAT 8430 spectrometer operating at an ionization potential of 70 eV was used for mass spectra. Shimadzu IR-460 spectrometer was employed for IR spectra. BRUKER DRX-500 AVANCE spectrometer at 500.1 and 125.8 MHz was used for 1H, and 13C NMR spectra for solutions in DCl3 with TMS as internal standard or 85% H3PO4 as external standard, respectively. Results: We describe a facile and green synthetic method for the synthesis of thiazole derivatives 5 from acid chlorides, potassium thiocyanate, alkyl bromides and amino acids using NR-ZnO- as the catalyst in water at room temperature. Conclusion: In conclusion, we describe an efficient, green procedure and high yielding synthesis of thiazole derivatives using acid chlorides, potassium thiocyanate, alkyl bromides and amino acids in the presence of NR-ZnO as the catalyst in water at room temperature.
Keywords: multicomponent reactions